Legal Analysis of Victim Negligence at Railway Crossings : a Case Study of Train Accident in Karawang and Government Legal Responsibility in Enhancing Public Safety - Karunia, Karunia; Lestari, Megha Ayu; Usnan, Amar; Hosnah, Asmak Ul (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study analyzes the legal implications of victim negligence in railway crossing accidents, focusing on a fatal case in Karawang, West Java. Using normative legal research and qualitative analysis, the study examines the incident's chronology, evaluates victim negligence under Law No. 23 of 2007 on Railways, and assesses government responsibilities. Findings reveal that victim negligence stems from low safety awareness and weak enforcement of safety regulations. Despite existing legal frameworks, implementation remains inadequate. The study highlights the need for stricter law enforcement, public education, and improved safety infrastructure. It emphasizes the government’s role in proactive accident prevention to enhance railway safety and inform policy recommendations.